Forgiveness therapy an empirical guide for resolving anger and restoring hope - Enright, Robert D. (American Psychological Association, 2015)
"In its second edition, Helping Clients Forgive, now retitled Forgiveness Therapy, benefits from more than a decade of new research into the innovative and growing field of forgiveness therapy. Forgiveness has been found to be a pivotal process in helping clients resolve anger over betrayals, relieve depression and anxiety, and restore peace of mind. For 30 years, the authors have pioneered these techniques, and here explain the process of forgiveness in psychotherapy in a way that can be applied by clinicians regardless of their theoretical orientation. With brand new chapters, studies, and models, clinicians will learn how to recognize when forgiveness is an appropriate client goal, how to introduce and explain to clients what forgiveness is and is not, and provide concrete methods to work forgiveness into therapy with individuals, couples and families. This comprehensive volume provides all of the latest research in the roles that anger and forgiveness play in specific emotional disorders and features clinical examples of work with individuals"--Publicity materials. (PsycINFO Database Record (c) 2014 APA, all rights reserved)